2018
DOI: 10.21037/jtd.2017.12.17
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in the prevention and follow-up of workers exposed to asbestos

Abstract: Although in most developed countries the use of asbestos is banned, there is still a consistent portion of the world where asbestos extraction, trading and manufacturing of asbestos-made products is largely diffuse. Worldwide, hundreds of millions of people are at risk of developing an asbestos caused disease because of occupational, environmental or domestic exposure. The WHO estimates that asbestos is responsible for more than 100,000 deaths yearly. This scenario has prompted the research on biomarkers poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…16,[39][40][41][42][43][44][45] Additionally, recent studies suggest that a combination of different biomarkers could improve the predictive capacity of SMRP. 41,42,44,46,47 Our present results show that genetic variability affecting the expression of these biomarkers should also be taken into account.…”
Section: Discussionmentioning
confidence: 62%
“…16,[39][40][41][42][43][44][45] Additionally, recent studies suggest that a combination of different biomarkers could improve the predictive capacity of SMRP. 41,42,44,46,47 Our present results show that genetic variability affecting the expression of these biomarkers should also be taken into account.…”
Section: Discussionmentioning
confidence: 62%
“…Apart from the most frequently studied biomarkers described above, some studies investigated other serum or plasma factors in asbestos-related diseases [83][84][85]. Among protein biomarkers, megakaryocyte potentiating factor and high mobility group box 1 (HMGB1) were increased in MM patients compared to healthy individuals or patients with benign asbestos-related diseases [84,85].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Additionally, novel studies suggest microRNA (miRNA) expression could also serve as a diagnostic or prognostic biomarker in MM [84][85][86]. Kirschner et al compared cell-free miRNA profiles in plasma from MM patients with healthy controls and proposed the potential role of miRNA-29c* and miRNA-92a as a candidate tumour biomarkers, and indicated that miRNA-625-3p is a promising novel diagnostic marker for MM [86].…”
Section: Other Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the challenges with diagnosis and unfavorable effect of late diagnosis on disease outcome, as well as the predicted burden of MPM in the future, there is excessive research interest in the discovery of potential biomarkers of MPM. Among them, studies on tissue and blood biomarkers (i.e., mesothelin, osteopontin, fibulin-3, high mobility group box-1 (HMGB1) protein, aquaporin 1, microRNAs, proteomics-based biomarkers) have shown promising results [19][20][21][22][23][24][25][26]. Soluble mesothelin related peptide (SMRP) is the most studied biomarker and has been approved by the Food and Drug Administration (FDA) to be used in MPM diagnosis.…”
Section: Introductionmentioning
confidence: 99%